SOME ECOLOGICAL STUDIES ON LINUM USITATISSIMUM LINN (Biological Sciences - PJSIR, 2004)
The application of fertilizers appeared to have no significant effect on the overall growth and productivity. Various salt types affected various parameters with a tendency of better growth in light textured soils. The plant grew better in full light condition with optimal soil moisture. The plants wilted to death under shady condition. Both the water stressed and water- logged conditions reduced the growth performance but the waterlogged condition adversely affected the plants. There- fore, it is concluded the L. usitatissimum could be grown in semi-arid condition on marginal lands.